Bridging Local Wisdom and Disciplinary Pedagogy: A Systematic Review of Trends in Ethnoscience-Integrated Science Instructional Models - Yanti Juanita; Laifa Rahmawati (Assyfa Learning Journal, 2026)
Background: 21st-century science education demands that students possess scientific literacy and critical thinking skills applicable to real-life scenarios. Integrating ethnoscience as local wisdom serves as an innovative instructional design to connect formal science with cultural context, successfully bridging the gap between high-level disciplinary knowledge and effective pedagogy. Objective: This study aims to analyze the publication trends of ethnoscience-integrated science learning models, identify the dominant instructional frameworks utilized, and describe their impact on educational outcomes. Method: Following the PRISMA guidelines, a Systematic Literature Review (SLR) was conducted on 10 Scopus-indexed articles published between 2015 and 2025, which were selected via strict inclusion criteria and evaluated using narrative synthesis. Results: The findings reveal an increasing trend in publications from 2023 to 2025, heavily focusing on scientific literacy and critical thinking. Dominant instructional designs include inquiry learning, ETNO-STEAM, context-based learning, and digital e-learning platforms. Implementing these models significantly enhances students' scientific literacy, higher-order thinking skills, learning motivation, and cultural identity reinforcement. Conclusion: Ethnoscience serves as a strategic instructional transformation pathway that seamlessly aligns science disciplines, cultural heritage, and character building within modern learning ecosystems.